Factors Contributing to the High Malignancy Level of Cholangiocarcinoma and Its Epidemiology: Literature Review and Data - Xuan Li; Renchu Guan; Shuangquan Zhang (Biology)
CCA is a highly desmoplastic malignant cancer and is the second most common primary liver malignancy after hepatocellular carcinoma (HCC), accounting for approximately 15% of all primary liver tumors. CCA has a poor prognosis, with an average five-year survival rate of 9%, which is lower than that of pancreatic cancer. Although considerable efforts have been invested into the genomics, epigenetics, and risk factors, very little is known about what might have been the key causes for the high malignancy level of CCA. In this review, we analyze the incidence and mortality of CCA in different regions based on data from 1994 to 2022 obtained from the International Agency for Research on Cancer (IARC), discuss the current status of treatment of the disease, and focus on what might be the main factors contributing to the high malignancy level of CCA: alkalosis caused by the Fenton reaction, hypoxia, and the TIME. The review includes studies published from 1979 to 2024, aiming to provide an updated synthesis of basic early classical theoretical knowledge and current knowledge about CCA. By revealing the epidemiological characteristics of CCA, the potential mechanisms of high malignancy, and the current challenges of treatment, this review aims to provide new directions for future cancer research, promote the development of personalized treatment strategies, and facilitate a deeper understanding and the more effective management of CCA worldwide.